Sovereignty in Antarctica: The Anglo-Argentine Dispute - MacKechnie, Russell W., Jr. (SURFACE at Syracuse University, 1977)
The purpose of this article is to examine the relevant arguments of Argentina and Great Britain and, in light of an analysis of the theories of territorial sovereignty and prior decisions, to suggest that, should the dispute be referred for decision to the International Court of Justice, Argentina has a formidable array of arguments at her disposal. It may be argued that the opportunity for decision by the Court is foreclosed by the existence of the Antarctic Treaty, that the issue of territorial sovereignty in Antarctica is moot. It is submitted, however, that the possibility of a Court determination is a substantial one for three significant reasons outlined in the paper.